PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA DEPARTEMEN HOUSEKEEPING APARTEMEN THE PAKUBUWONO SPRING JAKARTA SELATAN - Kiki Adrian; Liawati Liawati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The objective of this study is to examine the effect of compensation and work discipline on employee work productivity in the Housekeeping Department of The Pakubuwono Spring Apartment, South Jakarta, both partially and simultaneously. This study employs a quantitative research method. The sampling technique used is the Saturated sample method, resulting in a total sample of 60 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study are as follows: The analysis of the effect of the compensation variable (X1) on employee work productivity (Y) is based on the regression equation Y = 4.415 + 1.243X1. The correlation coefficient value is 0.661, indicating a strong relationship between the two variables. The coefficient of determination shows that compensation contributes 43.7% to employee work productivity, while the remaining 56.3% is influenced by other factors. Based on the hypothesis test, the calculated t-value is greater than the t-table value (7.162 > 2.001); therefore, H₀ is rejected and H₁ is accepted. This indicates that compensation has a significant effect on employee work productivity in the Housekeeping Department of The Pakubuwono Spring Apartment, South Jakarta. The analysis of the effect of the work discipline variable (X2) on employee work productivity (Y) is based on the regression equation Y = 7.427 + 1.137X2. The correlation coefficient value is 0.711, indicating a strong relationship between the two variables. The coefficient of determination shows that work discipline contributes 50.6% to employee work productivity, while the remaining 49.4% is influenced by other factors. Based on the hypothesis test, the calculated t-value is greater than the t-table value (7.838 > 2.001); therefore, H₀ is rejected and H₂ is accepted. This indicates that work discipline has a significant effect on employee work productivity in the Housekeeping Department of The Pakubuwono Spring Apartment, South Jakarta.Furthermore, the simultaneous effect of compensation (X1) and work discipline (X2) on employee work productivity (Y) is based on the regression equation Y = 4.755 + 0.375X1 + 0.865X2. The correlation coefficient value between the independent variables and the dependent variable is 0.853, indicating a strong relationship. The coefficient of determination shows that compensation and work discipline simultaneously contribute 51.7% to employee work productivity, while the remaining 48.3% is influenced by other factors. Based on the hypothesis test, the calculated F-value is greater than the F-table value (27.439 > 3.160); therefore, H₀ is rejected and H₃ is accepted. This means that compensation and work discipline simultaneously have a highly significant effect on employee work productivity in the Housekeeping Department of The Pakubuwono Spring Apartment, South Jakarta.